Enhanced osteogenic activity and anti-inflammatory properties of Lenti-BMP-2-loaded TiO2 nanotube layers fabricated by lyophilization following trehalose addition - Zhang X (Dove Medical Press, 2016)
Xiaochen Zhang,1 Zhiyuan Zhang,1 Gang Shen,2 Jun Zhao2 1Department of Oral and Maxillofacial Surgery, 2Department of Orthodontics, College of Stomatology, Ninth People’s Hospital, School of Medicine, Shanghai Jiao Tong University, Shanghai, People’s Republic of China Abstract: To enhance biocompatibility and osseointegration between titanium implants and surrounding bone tissue, numerous efforts have been made to modify the surface topography and composition of Ti implants. In this paper, Lenti-BMP-2-loaded TiO2 nanotube coatings were fabricated by lyophilization in the presence of trehalose to functionalize the surface. We characterized TiO2 nanotube layers in terms of the following: surface morphology; Lenti-BMP-2 and trehalose release; their ability to induce osteogenesis, proliferation, and anti-inflammation in vitro; and osseointegration in vivo. The anodized TiO2 nanotube surfaces exhibited an amorphous glassy matrix perpendicular to the Ti surface. Both Lenti-BMP-2 and trehalose showed sustained release over the course of 8 days. Results from real-time quantitative polymerase chain reaction studies demonstrated that lyophilized Lenti-BMP-2/TiO2 nanotubes constructed with trehalose (Lyo-Tre-Lenti-BMP-2) significantly promoted osteogenic differentiation of bone marrow stromal cells but not their proliferation. In addition, Lyo-Tre-Lenti-BMP-2 nanotubes effectively inhibited lipopolysaccharide-induced interleukin-1β and tumor necrosis factor-α production. In vivo, the formulation also promoted osseointegration. This study presents a promising new method for surface-modifying biomedical Ti-based implants to simultaneously enhance their osteogenic potential and anti-inflammatory properties, which can better satisfy clinical needs. Keywords: osteogenesis, anti-inflammation, TiO2 nanotube layers, Lenti-BMP-2, lyophilization, trehalose